First Nations and the Constitution: A Question of Trust - Slattery, Brian (Osgoode Digital Commons, 1992)
This article argues that the fiduciary relationship between Aboriginal peoples and the Crown is a special instance of a general doctrine of collective trust that animates the Canadian Constitution as a whole. This doctrine sheds light on the federal structure of Canada the unique status of Quebec, and the position of First Nations as a self-governing polities within Confederation. The article explores the origins and character of the constitutional trust, and considers its application to issues surrounding the inherent Aboriginal right ofself-government and Aboriginal land rights.